Safety and Long-Term Efficacy of Drug-Coated Balloon Angioplasty following Rotational Atherectomy for Severely Calcified Coronary Lesions Compared with New Generation Drug-Eluting Stents - Katsumi Ueno; Norihiko Morita; Yoshinobu Kojima; Hiroshi Takahashi; Masanori Kawasaki; Ryuta Ito; Hiroki Kondo; Shingo Minatoguchi; Tamami Yoshida; Yasumasa Hashimoto; Tomohiko Tatsumi; Tomoya Kitamura (Journal of Interventional Cardiology)
Objectives. This study sought to assess the safety and long-term efficacy of drug-coated balloons (DCB) following aggressive intracoronary image-guided rotational atherectomy (iRA) for severe coronary artery calcification (CAC), and to compare this strategy with new generation drug-eluting stents (nDES) following iRA. Background. Ischemic events following the treatment of CAC is still relatively high. Thus, more innovative strategies are required. Methods. We evaluated 123 consecutive patients (166 lesions) with de novo CAC undergoing an iRA (burr size; 0.7 of the mean reference diameter by intracoronary imaging) followed by DCB (DCB-iRA; 54 patients, 68 lesions) or nDES (nDES-iRA; 69 patients, 98 lesions). Follow-up angiography was obtained at > 6 months. Results. The target vessels (right coronary and circumflex), bifurcation (67.6% versus 47.9%), reference diameter (2.28mm versus 2.49mm), and lesion length (11.89mm versus 18.78mm) were significantly different between the two groups. The median follow-up was 732 days. TLR and TVR in DCB-iRA and nDES-iRA at 3 years were similar: 15.6% versus 16.3% (P=0.99) and 15.6% versus 23.3% (P=0.38). In 41 well-matched lesion pairs after propensity score analysis, the cumulative incidence of TLR and TVR in DCB-iRA and nDES-iRA at 3 years was 12.9% versus 16.3% (P=0.70) and 12.9% versus 26.1% (P=0.17), respectively. On QCA analysis, although the acute gain was smaller in DCB-iRA (0.85 mm versus 1.53 mm, P<0.001), the minimum lumen diameter at follow-up was similar (1.69 mm versus 1.87 mm, P=0.29). The late lumen loss was lower (0.09 mm versus 0.52 mm, P=0.009) in DCB-iRA. Conclusions. DCB-iRA is feasible for CAC.